Generation of SARS-CoV-2 Spike Pseudotyped Virus for Viral Entry and Neutralization Assays: A 1-Week Protocol - Condor Capcha, Jose Manuel; Lambert, Guerline; Dykxhoorn, Derek M.; Salerno, Alessandro G.; Hare, Joshua M.; Whitt, Michael A.; Pahwa, Savita; Jayaweera, Dushyantha T.; Shehadeh, Lina A. (Frontiers in Cardiovascular Medicine, 2021)
The COVID-19 pandemic caused by the SARS-CoV-2 coronavirus requires reliable assays for studying viral entry mechanisms which remains poorly understood. This knowledge is important for the development of therapeutic approaches to control SARS-CoV-2 infection by permitting the screening for neutralizing antibodies and other agents that can block infection. This is particularly important for patients who are at high risk for severe outcomes related to COVID-19. The production of pseudotyped viral particles may seem like a daunting task for a non-virology laboratory without experience in the two most commonly used pseudotyping systems, namely retro/lentiviruses and vesicular stomatitis virus (VSV) which lacks the VSV envelope glycoprotein (VSV-G). By incorporating the most up-to-date knowledge, we have developed a detailed, easy-to-follow novel protocol for producing SARS-CoV-2 spike-bearing pseudovirus using the VSV-G system. We describe the infection assay which uses GFP fluorescence as a measure of infection in a 24-well live imaging system. We present results of our optimization of the system to enhance viral infection levels through the over-expression of human ACE2 receptor and the overexpression of at least one of two proteases - TMPRSS2 or Furin, as well as, supplementation with Poloxamer 407 (P407) and Prostaglandin E2 (PGE2) as adjuvants. We show that the system works efficiently in 3 unrelated, clinically relevant cell lines: human 293T (renal epithelial) cells, human Calu-3 (lung epithelial) cells, and the non-human primate (African Green Monkey) cell line, Vero-E6 (renal epithelial) cells. In addition, we have used this system to show infection of human induced pluripotent stem cell-derived cardiomyocytes (iPS-CMs). This system is efficient (virus generation, titration, and infection assays can be performed in one week), quantitative, inexpensive, and readily scalable for application in drug development and therapeutic screening approaches.